2015
DOI: 10.2527/jas.2015-8956
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental temperature and dietary manganese on egg production performance, egg quality, and some plasma biochemical traits of broiler breeders1

Abstract: An experiment was conducted to investigate the effects of environmental temperature and dietary Mn on egg production performance, egg quality, and some plasma biochemical traits of broiler breeders. A completely randomized factorial design involved 2 environmental temperatures (a normal temperature, 21 ± 1°C, and a high temperature, 32 ± 1°C) × 3 dietary Mn treatments (a Mn-unsupplemented corn–soybean meal basal diet or the basal diet supplemented with 120 mg of Mn/kg of diet as either MnSO4·H2O or manganese p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 35 publications
2
18
0
Order By: Relevance
“…Heat stress is believed to produce ROS and induce oxidative damage in broilers (31,32) and laying hens (6) . In the current study, HT showed a clear trend towards elevating breast muscle MDA content and the increased plasma MDA level was also observed in our another study (17) , suggesting that lipid peroxidation occurs under the HT condition. However, at the same time, HT led to an increase in MnSOD activity in breast muscle.…”
Section: Discussionmentioning
confidence: 48%
See 4 more Smart Citations
“…Heat stress is believed to produce ROS and induce oxidative damage in broilers (31,32) and laying hens (6) . In the current study, HT showed a clear trend towards elevating breast muscle MDA content and the increased plasma MDA level was also observed in our another study (17) , suggesting that lipid peroxidation occurs under the HT condition. However, at the same time, HT led to an increase in MnSOD activity in breast muscle.…”
Section: Discussionmentioning
confidence: 48%
“…Relative moisture in the two rooms was kept at 40 (SEM 5) % during the experimental period of 14 weeks (32-45 weeks of age). Our previous results (17) on rectal temperature indicated that all of the laying broiler breeders under HT were in a heat stress status throughout the experimental period. The daily feed intake of birds in each replicate was recorded and reported previously (17) .…”
Section: Birds and Dietsmentioning
confidence: 99%
See 3 more Smart Citations